2004
DOI: 10.1111/j.1875-595x.2004.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-levels of fluoride in plaque and saliva and their effects on the demineralisation and remineralisation of enamel; role of fluoride toothpastes

Abstract: Aim: To summarise support for current consensus on the likely means by which fluoride toothpastes reduce caries and review some relevant studies of the effect of low levels of fluoride on the demineralisation and remineralisation of enamel. The major anti‐caries effect of fluoride toothpastes is thought to result from small but protracted elevations in levels of fluoride in plaque and saliva. Fluoride incorporated into enamel systemically does not reduce enamel solubility sufficiently to exert an anti‐caries e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 26 publications
5
84
0
9
Order By: Relevance
“…The daily topical application of fl uoride via toothbrushing strengthened enamel and healed the early carious lesion. 2,3 Dental caries is, however, not the only oral health care problem that the dental team is Dental caries and periodontal disease are the most common oral conditions experienced by adults today. The treatment of these diseases by the dental team can only be performed when patients attend dental practices.…”
Section: Introductionmentioning
confidence: 99%
“…The daily topical application of fl uoride via toothbrushing strengthened enamel and healed the early carious lesion. 2,3 Dental caries is, however, not the only oral health care problem that the dental team is Dental caries and periodontal disease are the most common oral conditions experienced by adults today. The treatment of these diseases by the dental team can only be performed when patients attend dental practices.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the profound effect of fluoride on enamel demineralisation and remineralisation that resulted from regular use of toothpaste, even with low levels of fluoride (Bowen, 1995, Lynch et al, 2004.…”
Section: Fluoridementioning
confidence: 99%
“…The low levels of fluoride are those found after many hours on resting dental plaque and saliva, and resulting from the regular use of fluoride toothpastes. Another source of low levels of fluoride are the constant exposure to this substance from water, milk, salt or whatsoever source is available on the oral environment (Lynch et al, 2004).…”
Section: How Much Fluoride Is Necessary?mentioning
confidence: 99%